The fungicidal effect of Rosa Damascena Mill extracts against fungal infections invading Plants in Al Taif - Ali Dosh Mohammed Hassan; Alamri Saleh Hamdan; Al-Ghamdi Saleh Bakheet; Al-Zahrani Salma A.; El-Sayed Sahar A.; Melebari Mohammad; Gazi Khaled S.; Alharthi Haitham Abdulrahman S.; Al-Mutairi Salman Faleh; Thabet Mohammed A.; Almiman Bandar Fahad (BIO Web of Conferences)
Plant pathogens of fungus have become of the most crucially harmful objects that may affect overall plants growth rate and crops production worldwide. This study involved the identification of six species and six genera was achieved from the ten fungal plant pathogen isolates that gathered from different sites and regions in Taif region, Saudi Arabia. The identification of these organisms was conducted using molecular markers; among the identified species, 30% were Mucor circinelloides, 20% were Penicillium crustosum, and 20% were Alternaria alternata. The remaining 30% was comprised of Cladosporium tenuissimum, Phoma macrostoma, and Fusarium equiseti. A considerable proportion of these genera are widely acknowledged for their capacity to generate mycotoxins. The linear growth regression derived by the new plant extract is higher than fungicide, it has been found that the growth inhibition percentage driven by fungicide was between (20 to 85%), whereas for plant extract was between (80 to 100%) across all isolates. This data facilitate the contributing to the exploration of a more secure alternative to fungicides. Further, it will facilitate the development of regulatory approaches aimed at alleviating the detrimental consequences of fungal infections.